Peran guru pendidikan agama islam dalam penguatan pendidikan karakter islam pada peserta didik generasi z - ardiwati, diva aliyah (Maliki Interdisciplinary Journal, 2026)
Islamic character education is a crucial part of the national education system, particularly in shaping the morals and religious identity of Generation Z students living in the digital age. This article discusses the role of Islamic Religious Education (PAI) teachers in strengthening Islamic character education for Generation Z through pedagogical approaches, role models, and adaptation to technological developments. Through a review of the latest literature and an analysis of contemporary educational phenomena, it was found that PAI teachers act as educators, spiritual guides, facilitators, and moral role models. However, challenges such as changes in student learning styles, the rapid flow of digital information, low interest in religious learning, and teachers' limited digital pedagogical competencies pose obstacles to its implementation. This article concludes that strengthening Islamic character education for Generation Z requires innovative learning methods, collaboration with parents and the school environment, and strengthening the professionalism of PAI teachers. Practical recommendations are presented as an effort to strengthen the implementation of Islamic character education in the context of modern education.